Implementation of Targeted Education to Promote Normal Vaginal Delivery: A Randomized Controlled Trial - Khadijeh Mohammadali Makhouli; Marzieh Araban; Akbar Hassanzadeh; Zamani Alavijeh (Mashhad University of Medical Sciences, 2018)
Introduction: It is widely reported that the complications of Caesarean-section (C- section) delivery are much more than the normal vaginal delivery (NVD) in Iran. The purpose of this study was to determine the effect of targeted education on the mode of delivery in pregnant women. Methods: A randomized controlled trial was conducted among 72 primiparous women at their 20-25 weeks of gestational age in Isfahan, Iran, during 2015. The sample was randomized into two groups of 36 people. A pre-test was performed using a questionnaire on knowledge, attitude, perceived self-efficacy, perceived social support, and intention to choose the delivery mode. The experimental group (including the women and their spouses) received specialized educational messages in a form of a computer file based on their scores obtained from each part of the pre-test data. At 37 weeks of pregnancy, post-test was administered to both study groups using the questionnaire and the mode of delivery was recorded in the questionnaire after the birth. The analysis of data was conducted using SPSS through the Chi-square test, independent t-test، and paired t-test. Results: Before the intervention, no significant difference was observed in terms of the studied variables between two the groups (P=0.71). However, the mean score in the experimental group was higher than that of the control group after the intervention (P<0.001). The definite decision to choose NVD in the experimental group also increased from 30.6% to 58.3% which was significantly more than that of the control group (P=0.03). The frequency of NVD was significantly higher in the experimental group, compared to the control group (P=0.04). Conclusion: The utilization of targeted educational messages through computer based on knowledge, self-efficacy, attitude, and perceived social support could result in NVD selection. Therefore, it is suggested to provide new strategies to offer educational messages, such as targeting education in community health centers.